2018
DOI: 10.1016/j.molliq.2018.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism for reduction of Pt(IV) anticancer model compounds by Se-methyl L-selenocysteine. Comparison with L-selenomethionine

Abstract: Se-methyl L-selenocysteine (MeSeCys) is one of the major organic selenium compounds acquired from the diet by human beings. It has been shown to have anticancer activity and cancer prevention functions. However, its antioxidant activity, largely related to its biological function, has not been well characterized so far. We here report a stopped-flow kinetic study of the reduction of the Pt(IV) anticancer model compounds trans-[PtX 2 (CN) 4 ] 2− (X = Cl; Br) by MeSeCys in a wide pH range. Overall second-order k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Our , respectively, are reduced much faster. 17,32 Hence, our earlier findings are against the reaction mechanism illustrated in Figure S8. 17,32…”
Section: Calculations Of Rate Constants Of the Rate-determining Stepsmentioning
confidence: 56%
See 1 more Smart Citation
“…Our , respectively, are reduced much faster. 17,32 Hence, our earlier findings are against the reaction mechanism illustrated in Figure S8. 17,32…”
Section: Calculations Of Rate Constants Of the Rate-determining Stepsmentioning
confidence: 56%
“…A spectrophotometric titration approach was opted to study the reaction stoichiometry of the present redox processes. [32][33][34] was estimated from the intersection point. Essentially, the estimated ratio is very close to a theoretical stoichiometry of 1:2 if CA was assumed to be oxidized to CA disulfide (H 2 NCH 2 CH 2 SSCH 2 CH 2 NH 2 or CA-disulfide) as expressed by Equation 3:…”
Section: Stoichiometric Ratios For the Redox Reactionsmentioning
confidence: 99%
“…The stoichiometry of the reaction between [Pt(cdbca)(NH 3 ) 2 Cl 2 ] and ascorbate was studied by the spectrophotometric titration method described earlier [23,37,38,39]. A series of reaction mixtures were prepared in a phosphate buffer at pH 7.40 with [Asc] tot = 0.10 mM kept constant, whereas [Pt(IV)] was varied between 0 and 0.30 mM.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent agreement between experimental data and theoretical simulations shown in Figure 5 and Figure 6 bolsters the validity of the reaction mechanisms given in Figure 7 and Figure S3. By use of the obtained rate constants in Table 2 and the p K a values for the various protolytic species [54,56], the reactivity of the various Cys and GSH species in the reduction of cis,trans -[Pt(cbdca)(NH 3 ) 2 Cl 2 ] was analyzed in terms of reactivity versus pH distribution diagrams [38,39]. These are shown in Figure S5 for Cys and in Figure S6 for GSH in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
“…Considering SeMet in the existing species of organic Se, they have negative charges and provide the electrostatic interactions, facilitating the combination with positive charged Pb 2+ . However, Se IV is always positive charge and generates repulsion with Pb 2+ , resulting in a decrease in the content of Pb 2+ (Liu et al ., 2018). It indicated that SPHs‐2 has a better availability to chelate Pb 2+ , and SeMet plays an important role in reducing Pb 2+ penetration.…”
Section: Discussionmentioning
confidence: 99%